Bibliometric Analysis of Ferroptosis in Stroke From 2013 to 2021 - Chen, Yuhua; Long, Tianlin; Xu, Quanhua; Zhang, Chi (Frontiers in Pharmacology, 2022)
Background: Stroke is a major cause of long-term disability and death, and the clinical therapeutic strategy for stroke is limited and more research must be conducted to explore the possible avenues for stroke treatment and recovery. Since ferroptosis is defined, its role in the body has become the focus of attention and discussion, including in stroke. Methods: In this work, we aim to systematically discuss the “ferroptosis in stroke” researches by bibliometric analysis. Documents were retrieved from the Web of Science Core Collection database on October 30, 2021. Statistical analysis and visualization analysis were conducted by the VOSviewer 1.6.15. Results: 99 documents were identified for bibliometric analysis. The researches on “ferroptosis in stroke” was rapidly developing and which remained the focus of many scholars and organizations in the last few years, but the Chinese groups in this field still lacked collaboration with others. The documents and citation analysis suggested that Rajiv R. Ratan and Brent R. Stockwell were active researchers, and the researches of Qingzhang Tuo, Ishraq Alim, and Qian Li are more important drivers in the development of the field. Keywords associated with lipid-peroxidation, ferroptosis, iron, oxidative stress, and cell death were high frequency, but apoptosis, necroptosis, pyroptosis, and autophagy were a shortage of research and there may be more research ideas in the future by scholars. Conclusion: Further exploring the mechanisms of crosstalk between ferroptosis and other programmed cell death improves clinical applications and therapeutic effects against stroke. The scholars will also continue to pay attention to and be interested in the hot topic “ferroptosis in stroke”, to produce more exciting results and provide new insights into the bottleneck of stroke treatment.